Anak Muda Kristen Peduli Lingkungan Hidup - Eunike Clarisa Nababan; Irmawaty Nengsih Togatorop; Angelica Petrina Sianturi; Emya Natalia Ginting; Damayanti Nababan (Publisher STPKat, 2022)
Environmental ethics in Indonesia or in the world is very important to be maintained and also preserved because this environmental ethics is one of the ethics that has a very positive influence on everyone's life. Environmental ethics is the moral wisdom of humans in dealing with their environment, this environmental ethics is needed by every individual, especially Christians. So that every activity related to the environment is considered carefully so that the sustainability and comfort of the environment are maintained. One of the problems is the issue of environmental ethics, the lack of awareness that it is very important to keep the environment clean in order to maintain the comfort of each individual. As young Christians, we must be concerned about this very deficient state of environmental ethics, because God Himself has given a mandate to young Christians to be good managers of all that He entrusts to believers, including the environment around us. And it is entrusted that the role of youth is very large in environmental ethics.